2022
DOI: 10.1093/cercor/bhab455
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar signals drive motor adjustments and visual perceptual changes during forward and backward adaptation of reactive saccades

Abstract: Saccadic adaptation ($SA$) is a cerebellar-dependent learning of motor commands ($MC$), which aims at preserving saccade accuracy. Since $SA$ alters visual localization during fixation and even more so across saccades, it could also involve changes of target and/or saccade visuospatial representations, the latter ($CDv$) resulting from a motor-to-visual transformation (forward dynamics model) of the corollary discharge of the $MC$. In the present study, we investigated if, in addition to its established role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 90 publications
(109 reference statements)
1
21
0
Order By: Relevance
“…Because of its circular learning architecture, its visuospatial maps and its CD projection pathway to frontal cortex (Middleton & Strick, 2000), the cerebellum is an ideal candidate to also recalibrate the visuospatial target map and the forward dynamics model. In Cheviet et al (2022), we found first evidence that changes in visuospatial representations during saccadic motor learning are impaired in cerebellar patients.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Because of its circular learning architecture, its visuospatial maps and its CD projection pathway to frontal cortex (Middleton & Strick, 2000), the cerebellum is an ideal candidate to also recalibrate the visuospatial target map and the forward dynamics model. In Cheviet et al (2022), we found first evidence that changes in visuospatial representations during saccadic motor learning are impaired in cerebellar patients.…”
Section: Introductionmentioning
confidence: 75%
“…Consistent with previous studies (Moidell & Bedell, 1988; Collins et al, 2007; Hernandez, Levitan, Banks, & Schor, 2008; Schnier et al, 2010; Zimmermann & Lappe, 2010; Gremmler et al, 2014; Masselink & Lappe, 2021), we found a small change of V 1 in learning direction for control subjects (inward -0.7 ± 2.0°, t 7 = -1.00, p = .351; outward 1.2 ± 1.8°, t 7 = 1.86, p = .105; Figure 3A-1). Please note that in the analysis of Cheviet et al (2022) (which comprised more trials including those in which the flash was presented with a small distance to the 20° target position), these changes were subtly significant. Accordingly, the visual gain ω v of control subjects adapted by -0.04 ± 0.10 ( t 7 = -1.00, p = .351; Figure 4B) in the inward condition and 0.06 ± 0.09 ( t 7 = 1.86, p = .105; Figure 4D) in the outward condition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations